Wolontariat osób starszych jako element wychowania w perspektywie starości – wybrane aspekty - Tomasz Słabiak (Edukacja Ustawiczna Dorosłych, 2022)
The following article focuses on the role of social activity with particular emphasis on the voluntary work of the elderly as an important aspect of education in old age. Volunteering allows an elderly person to properly adapt to the old age and to understand the changes taking place. It also contributes to improving the quality of life in its declining phase. The purpose of the article is to describe the importance of voluntary activities in old age.